Single-molecular diffusivity and long jumps of large organic molecules: CoPc on Ag(100) - Sabik, Agata; Ellis, John; Hedgeland, Holly; Ward, David J.; Jardine, Andrew P.; Allison, William; Antczak, Grażyna; Tamtögl, Anton (Frontiers in Chemistry, 2024)
Energy dissipation and the transfer rate of adsorbed molecules do not only determine the rates of surface chemical reactions but are also a key factor which often dictates the growth of organic thin films. Here, we present a study of the surface dynamical motion of cobalt phthalocyanine (CoPc) on Ag(001) in reciprocal space based on the helium spin-echo technique in comparison with previous scanning tunnelling microscopy studies. It is found that the activation energy for lateral diffusion changes from 150 meV at 45-50 K to ≈100 meV at 250-350 K, and that the process goes from exclusively single jumps at low temperatures to predominantly multiple jumps at high temperatures. We thus illustrate that while the principles of molecular motion remain valid, upon comparing the same dynamical process over widely divergent time scales, indeed different answers are found. Hence a precise molecular level understanding of dynamical processes and thin film formation requires to follow the dynamics over the entire temperature scale relevant for the process. Furthermore, we determine the diffusion coefficient and the atomic-scale friction of CoPc and establish that the molecular motion on Ag(001) follows from a low friction scenario as a consequence of the additional molecular degrees of freedom.